2022
DOI: 10.1002/ange.202205385
|View full text |Cite
|
Sign up to set email alerts
|

Anion‐Guided Stepwise Assembly of High‐Nuclearity Lanthanide Hydroxide Clusters

Abstract: The ability to construct complex molecular architectures with precise control is critical for realizing molecule-based materials and functions. Using the assembly of a 60-metal complex of Er III with histidine as an example, we demonstrate the rational assembly of otherwise synthetically elusive polynuclear lanthanide hydroxide clusters directed by the combined set of I À and CO 3 2À as templates. We succeeded in the stepwise transformation starting from Er 12 to Er 60 by way of two key intermediates Er 34 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The outstanding advantage of metal clusters is their definite atomic composition and the well-defined geometrical structure, which can be modulated by changing the internal atoms and surface ligands [13][14][15][16][17]. Considerable efforts in this field have resulted in the fabrication of a large number of LnOCs based on organic ligands [18][19][20][21][22][23]. Compared with organic ligand-protected LnOCs, inorganic ligand-protected LnOCs have higher thermal stability and unique rigid structures [24][25][26].…”
Section: Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outstanding advantage of metal clusters is their definite atomic composition and the well-defined geometrical structure, which can be modulated by changing the internal atoms and surface ligands [13][14][15][16][17]. Considerable efforts in this field have resulted in the fabrication of a large number of LnOCs based on organic ligands [18][19][20][21][22][23]. Compared with organic ligand-protected LnOCs, inorganic ligand-protected LnOCs have higher thermal stability and unique rigid structures [24][25][26].…”
Section: Instructionmentioning
confidence: 99%
“…Up to now, large numbers of POMs-based LnOCs with a rich variety of structures and interesting properties have been reported. However, compared with the POMs-based 3d-transition metal clusters and organic ligand-based LnOCs, the development of POMs-based LnOCs is still lagging behind, and the synthesis of high-nuclearity LnOCs still lacks a proven method [18][19][20][21][22][23][38][39][40][41]. In this review, we summarize the development of the most widely studied LnOCs related to polyoxotungstates, including structural classification, synthesis strategies, and some properties, and briefly discuss our personal views on their future research directions.…”
Section: Instructionmentioning
confidence: 99%
“…In particular, this review revealed recent articles describing their extraction processes from various sources [1][2][3][4][5][6][7], as REE forms numerous compounds with inorganic and organic ligands. Indeed, a wide range of such compounds was examined, for instance halides, nitrates, sulfates, carbonates, phosphates, oxalates, hydroxides, and oxides, as well as double salts [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…24 Due to the variable coordination numbers, weak stereochemical bias and kinetic instability of lanthanide ions, research on the formation process and self-assembly mechanism of lanthanide clusters has been slow. [25][26][27] Although the exploration of the self-assembly mechanism of lanthanide clusters is still at the initial stage, we have made a series of progresses in this field. [28][29][30][31][32][33][34][35][36][37] In 2018, we were the first to use HRESI-MS to track the self-assembly process of triangular-shaped dysprosium clusters with toroidal magnetic moments.…”
Section: Introductionmentioning
confidence: 99%